2004
DOI: 10.1136/bmj.38226.605995.55
|View full text |Cite
|
Sign up to set email alerts
|

NHS Direct versus general practice based triage for same day appointments in primary care: cluster randomised controlled trial

Abstract: Objective To assess the relative effects on consultation workload and costs of off-site triage by NHS Direct for patients requesting same day appointments compared with usual on-site nurse telephone triage in general practice. Design Cluster randomised controlled trial. Setting Three primary care sites in York, England. Participants 4703 patients: 2452 with practice based triage, 2251 with NHS Direct triage. All consecutive patients making requests for same day appointments during study weeks were eligible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(70 citation statements)
references
References 6 publications
0
57
1
Order By: Relevance
“…White and the study of triage of same day appointment requests, CDSS use had no effect on the number of practice based consultations, emergency department consultations, and out of hours consultations in the month following triage. 22 When CDSS was used for glucose regulation in ICU, there was no effect on the proportion of time blood glucose levels were within the target range (risk difference 0.01, 95% CI -0.13 -0.15, p = 0.85). 19 In summary, in one study CDSS use improved performance measures, 19 in another it was associated with poorer performance, 22 and no study found an impact of CDSS on patient outcomes.…”
Section: Participants)mentioning
confidence: 99%
See 2 more Smart Citations
“…White and the study of triage of same day appointment requests, CDSS use had no effect on the number of practice based consultations, emergency department consultations, and out of hours consultations in the month following triage. 22 When CDSS was used for glucose regulation in ICU, there was no effect on the proportion of time blood glucose levels were within the target range (risk difference 0.01, 95% CI -0.13 -0.15, p = 0.85). 19 In summary, in one study CDSS use improved performance measures, 19 in another it was associated with poorer performance, 22 and no study found an impact of CDSS on patient outcomes.…”
Section: Participants)mentioning
confidence: 99%
“…Improved performance and patient outcomes were anticipated if the CDSS was effective. Targeted behaviours were anticoagulation management, 21 telephone triage of same day appointment requests, 22 and glucose regulation. 19 The studies by Richards et al 22 and Rood et al 19 assessed the impact of CDSS in terms of performance measures.…”
Section: Participants)mentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen studies reported impacts on their own service or other services, either from increased or reduced service use and or increased or reduced staff workload [68][69][70]86,95,98,99,[101][102][103]105,109,112,114,122,126,134 One study found that NHS Direct referred a higher proportion of patients to other services when compared with general practice. 134 A RCT by Lattimer et al 68 reported a 38% reduction in primary care appointments and a 23% reduction in home visits, whereas another study reported no change in primary care appointments but home visits reduced by 18%.…”
Section: Service Impactsmentioning
confidence: 99%
“…93,94 Costs Nine studies reported costs or cost savings. 75,79,86,101,[108][109][110][111][112]126 The most common method of calculating and reporting costs was to report costs saved from callers' change in subsequent health-care-seeking behaviour as a result of the call. 75,79,108,110 These were not consistently reported and were reported as average per patient savings, cost savings per call recommendation type, annual net savings and overall reduction, making comparison difficult.…”
Section: Safetymentioning
confidence: 99%